Water pollution and the assessment of water quality parameters: a review - Misman, Nurafifa Akmal; Sharif, Mohd. Faez; Chowdhury, Ahmed Jalal Khan; Azizan, Nur Hafizah (Desalination Publications, 2023)
The entry of pollutants into the water bodies has deteriorated the quality of freshwater which led to the occurrence of water pollution. The factors of water pollution due to natural processes are cli- mate change and natural disasters. The anthropogenic activities that affect water quality are urban- ization, development of infrastructures, industrial applications, agricultural activities, and sediment runoff. The severity of water pollution is measured using physical, chemical, and biological param- eters. For biological parameters, metagenomics analysis is associated with bioinformatics in detect- ing, identifying, and characterizing the microorganisms present in the environment. The methods carried out from the data analysis through the bioinformatics study are bacterial abundance, rar- efaction curve, core microbiome, clustering analysis and diversity analysis. Turbidity, temperature, electrical conductivity (EC), and total dissolved solids (TDS) are the physical parameters whereas pH, nutrients (ammoniacal nitrogen and phosphorus), dissolved oxygen (DO), and heavy met- als are the chemical parameters. A thorough and detailed study needs to be done to correlate the sources of water pollution and the water quality of freshwater. Therefore, proper treatment can be carried out to improve the water quality of the freshwater according to the class in DOE-WQI.